Who drives urban densification? Linking landownership and spatial dynamics - Ehrhardt, Denise; Sommer, Felicitas; Ndim , Mouhamadou; Raimbault, Juste; Hartmann, Thomas; Jehling, Mathias (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Cities worldwide have developed policies to promote and control urban densification. However, a high proportion of densification takes place without the purview of strategic planning. It is driven by individual landowners, who hold a strong position in deciding if land is developed or not. Despite their pivotal role, knowledge on landowner involvement is highly restricted by limited access to landowner data. We address this gap and make use of a unique dataset, available for the city of Dortmund, including landowner data for each parcel in 2011 and 2021. Using a geospatial approach, we identify six forms of densification, ranging from large-scale multi-family housing development to small-scale densification with low-density housing, and provide for the first time a systematic analysis of the involvement of private individuals, private companies and the municipality in these processes. The results show that private individuals play an important role in small-scale densification, which accounts for a third of all densification in Dortmund and takes place mainly in suburban areas. Further, we show that each densification type is associated with a distinct pattern of landownership and change of landownership over time. Our findings highlight the need for customised land policy approaches that can address private landowners’ interests, in order to facilitate and direct densification processes.
Keywords: Urban densification; Infill development; Landowner; Geospatial analysis; Land policy; Dortmund